Karakteristik Char Hasil Pirolisis Ban Bekas Pada Rotary Kiln - Surya Darmawan Hendra; Gatut Rubiono; Anas Mukhtar (Virtual of Mechanical Engineering Article, 2018)
The study was conducted with a pyrolysis experiment where temperature variation of 250oC, 350oC, 450oC, and 550oC and tire sample mass of 300 gram. The heating temperature comes from an electric heater equipped with a control system. The temperature was measured using K type thermocouple. The residence process was carried out for 120 minutes measured using a stopwatch. The tire and char sample volume were measured using measuring cups and the sample mass was measured using the scales. Tests on char quality characteristics include flame, coal temperature, flame time, and ash residue. The results showed that the higher the process temperature in pyrolysis, it affects char characteristics on the rotary kiln. The percentage of char mass losses tends to increase with the high pyrolysis process temperature. Char shrinkage factor tends to decrease as the percentage of mass loss increases. Char porosity tends to rise as the percentage of mass loss increases. The percentage of blue color on the char flame tends to rise in accordance with the addition of the percentage of mass loss and vice versa the percentage of red color on the char flame tends to decrease. The combustion temperature of char combustion tends to increase according to the high temperature of the pyrolysis process. Coal char's flame time tends to increase as char porosity increases. The ash of combustion yield tends to decrease as the percentage of mass loss increases.